Analysis of Business Exit Decision in Small and Medium Entreprises (SMEs) - Novita Ratna Satiti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to examine the influence of exit intention, firm performance, and motivation on business exit decisions in SMEs in the non-agricultural sector in Malang City. In addition, this study also evaluates the role of exit intention moderation on the relationship between company performance and motivation and business exit decisions. The population in this study is non-agricultural sector SMEs in Malang City which totals 37,715 SMEs based on data from the East Java Province Cooperatives and MSMEs Office in 2019. The results show that the intention to exit and the company's performance have a significant positive influence on the decision to leave the business, while motivation has a significant negative influence on the decision to leave the business. Further, exit intent does not significantly moderate the relationship between company performance and business exit decisions, but significantly moderates the relationship between business exit motivation and the decision to leave the business with negative influences. These findings provide important insights for SME management in managing the factors that affect business exit decisions so that they can take strategic steps to reduce the possibility of unwanted exits.